Evaluating public-participation processes: the case of the ULEAM Computer Science School - Santamaría Philco, Alex (2015)
This paper synthesizes an analysis of the implementation of a public participation program, which was conducted using a software prototype and experiments led by students and faculty at Universidad Laica Eloy Alfaro de Manabí. The objective was to collect data forfuture design of a standard methodology that uses information and communication technologies (ICT), and that can be adaptable to every application. Based on a theoretical background, we first specified a model representing the life cycle of every public participation process. In a second stage, we designed a support environment by using the Rational Unified Process (RUP), which enabled the public participation model to be automated. The model has two tools: the first one intended for public participation experts (developed with Visual Studio .Net), and the second one targeted to the general public (using PHP language web environment). Finally, the integration of the two applications, as well as their operating capacity, were evaluated through functional and non-functional tests, and through pilot testing with the participation of students and university faculty. The evaluations produced favorable results demonstrating the applicability of the application.